Perancangan dan Implementasi Platform Manajemen Repositori Berbasis Git Menggunakan Teknologi Open Source - Sugiyatno; Rahmad, Dwi Swasono; Syarif, Arief Rama (Melati Institute, 2025)
Modern software development requires efficient repository management systems to support collaboration and version control. GitHub is one of the dominant platforms, but its dependence on cloud-based services poses challenges related to privacy, security, and cost. This research aims to design and implement a Git-based repository management platform using open source technologies such as Gitea and GitLab CE as a self-hosted alternative to GitHub. The research method includes literature study, comparative analysis of the features and architecture of open source platforms, as well as system implementation and testing in a standalone server environment. The results show that Gitea is lighter and easier to implement than GitLab CE, which requires more resources but offers more DevOps features. Performance testing shows that Gitea has a faster response time on servers with limited specifications, while GitLab is more suitable for enterprise scale with complex CI/CD needs. In addition, the integration of AI for code review automation shows improved efficiency in detecting code smells and potential security vulnerabilities in source code. In conclusion, open source platforms such as Gitea and GitLab CE can be an alternative solution to GitHub with the advantages of flexibility, privacy, and full control over the repository. The results of this research can be a reference for organizations or institutions that want to implement a source code management system independently.